Serum enzyme response of captive sturgeon brookstock Acipenser baerii Brandt 1869 females and two hybrids (bester = female Huso huso Linnaeus, 1758 × male Acipenser ruthenus Linneaus, 1758, and RsSs = A. gueldenstaedtii Brandt 1833 × A. baerii Brandt 1869) to hormonal stimulation for spawning induction. (November 2015) - Barulin, N. V.
Summary: The objective of this study was to assess the response of three hepatic enzymes [aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP)] in sturgeon broodstock females to hormonal treatment during the spawning season. Acetone‐dried sturgeon pituitary was used for spawning induction in three cultured broodstocks ( Acipenser baerii, bester, and the RsSs hybrid). Blood samples were collected from females during the spawning seasons between 2011 and 2013. Hepatic enzyme activities AST, ALT, and ALP were higher in the non‐response of females to the hormone treatment. The differences were species‐specific. The increased levels could indicate either an inappropriate timing of the hormone treatment or potential liver disorders in these treated females.